Physicochemical, Sensory, Chemical Stability and Cost Evaluation of Beef Sausages Produced with Substitution of Fat with Bovine Blood - Pius M. Mathi (Journal of Medical and Health Sciences (JMHS), 2026)
The purpose of this study was to develop a nutrient-rich and shelf-stable beef sausage by partially replacing animal fat with bovine blood. Fat is a fundamental ingredient in sausage formulation; however, animal fat is increasingly being implicated in ill health worldwide, prompting processors to rethink sausage formulations and explore low-fat alternatives. Various fat substitutes have been tested, with varied results, while bovine blood is widely accepted as a food ingredient in Kenya. A completely randomised design was used with fat-to-blood ratios of 20:0, 15:5, 10:10, 5:15, and 0:20. The sausages were evaluated for sensory properties and analysed for proximate composition, texture, cooking loss, water-holding capacity, iron content, fat oxidation using peroxide value for keeping-quality determination, and cost. One-way ANOVA was used to analyse the data, while Duncan’s multiple range test was applied to determine differences among the means. Twenty untrained panellists with familiarity with sausages participated in the sensory evaluation. The findings showed that fat substitution with blood above 10% was not considered acceptable by the panellists. However, substitution significantly increased the protein, iron, and water contents of the sausages (p < 0.05), while reducing water-holding capacity and increasing cooking loss. Reducing the fat content of the sausages led to reduced peroxidation, with a 5 per cent fat level yielding a peroxide value as low as 6.4 meq/kg. The study concluded that it is possible to produce an acceptable fresh beef sausage by partially substituting up to 10 per cent of the fat with bovine blood, while also reducing production costs.